Robust time‐varying formation control for multiple underwater vehicles subject to nonlinearities and uncertainties - Liu, Hao; Lyu, Yafei; Lewis, Frank L.; Wan, Yan (International journal of robust and nonlinear control, 2019)
Summary This paper addresses the robust formation control problem for multiple autonomous underwater vehicles (AUVs) to achieve the desired formation trajectory and time‐varying formation pattern and to align the vehicle attitudes. The dynamics of each AUV system involves parameter variations, nonlinear dynamics, and external disturbances. A robust distributed formation control protocol is developed based on the graph theory and the robust compensation theory. It is proven that the tracking errors of the global uncertain system can converge into a given neighborhood of the origin in a finite time. Simulation results substantiate the effectiveness of the developed formation control method for multiple AUVs subject to nonlinearities and uncertainties.